Learning to read Talmud : what it looks like and how it happens - Kanarek, Jane L.; Lehman, Marjorie Suzan (Academic Studies Press, 2016)
The first book-length study of how teachers teach and how students learn to read Talmud. Through a series of classroom studies conducted by scholars of Talmud, this book elucidates a broad range of ideas about what it means to learn to read Talmud and tools for how to achieve that goal.